Consumer’s Buying Decisions of Schedule Domestic Passenger Flights in Indonesia - Yustisia Kristiana, Nonot Yuliantoro, Vasco A. H. Goeltom, Innocentius Bernarto, Rudy Pramono, Agus Purwanto (International Journal of Advanced Science and Technology, 2020)
The purpose of this study is to analyze and test: 1) does competitive price affect the decision to purchase an airplane tickets?; 2) does competitive price affect lifestyle?; 3) does promotion affect lifestyle?; 4) does promotion affect decision to purchase an airplane ticket?; 5) does lifestyle influences decision to purchase an airplane ticket?. The data collection in this study is done using questionnaire to schedule domestic passenger flights. The numbers of the respondents are 122 people. The sampling technique is done with convenience sampling. Partial Least Square-Structural Equation Modeling approach with SmartPls program is used for data analysis. The results show that competitive price, promotion, and lifestyle has a positive effect on consumer’s buying decisions of airline tickets. Similarly, promotion has a positive effect on lifestyle. Then, competitive price has a positive effect on lifestyle.